Pemberdayaan UMKM Melalui Digital Marketing dan Branding Produk pada UMKM Kerupuk Desa Bambayang Sukabumi. - Nispi Yani Sya'banniah; Shafa Shafiyyah Rahmatul Umma; Ingka Andriani; Muhamad Fachmi Ramadhan; Erni Yuningsih (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
This community service was carried out at Barokah Crackers UMKM, Bambayang Village, Cicurug District, Sukabumi Regency. This activity aims to empower MSMEs and provide knowledge and provide training to business actors in increasing competitiveness in this era of globalization. Because currently the economic condition has kept up with the times that all use digital in their business, but many MSMEs do not take advantage of it because they are unfamiliar with using electronics so that MSMEs are unable to compete with other products that are all online. The problem faced by Kerupuk Barokah SMEs is that there is no use of digital marketing in promoting their products and there is no implementation of branding . Digital marketing training, creating social media accounts and making packaging brand labels are expected to help MSMEs introduce their products to consumers to increase their competitiveness so that marketing can be carried out effectively and efficiently. In addition, training in recording financial reports is expected to help MSMEs become more informed about the calculation of the profit to be obtained and the estimated capital to be issued.